KARAKTERISTIK SENSORIS BISKUIT YANG TERBUAT DARI BEBERAPA JENIS TEPUNG KOMPOSIT - Kristof N. Ruata; Maria F. Sumual; Jenny E.A. Kandou (Universitas Sam Ratulangi, 2017)
Abstact Wheat flour biscuits mixed with local food starch is a development of food security. Generally flour and starch contain amylose and amylopectin with different amount composition. Mixing of wheat flour and some starch is tacca tuber starch, tapioca starch (sweet potato), starch sago starch and corn starch form different amylose and amylopetin content composition. Comparison of amylose and amylopectin levels affects texture, sensory properties and gelatinization temperature. This study aims to evaluate the physical characteristics of blending wheat flour with tacca starch (anuwun), cassava tuber starch, sago starch and corn starch, mixing function of starch and starch in forming sensory properties of biscuit. This study used Completely Randomized Design (RAL) with mixed flour and starch mixed flour treatment with 1: 1 ratio. All treatments were repeated 3 replications and the data were analyzed. The results of the most favorite aroma-level test on TTPT treatment, the highest color in TTPS treatment, the highest taste in TTPJ treatment and crispness in TTPJ treatment. Diversity of high level of preferences on biscuits of TTPS composite flour. The level of preference for the crispity of the TTPJ composite flour biscuit obtains the highest value that is consistent with the ranking of biscuit hardness. Each composite flour has different solubility characteristics and water absorption.